A Group Therapeutic Songwriting Intervention for Family Caregivers of People Living With Dementia: A Feasibility Study With Thematic Analysis - Baker, Felicity A.; Stretton-Smith, Phoebe; Clark, Imogen N.; Tamplin, Jeanette; Lee, Young-Eun C. (Frontiers in Medicine, 2018)
This study aimed to test the feasibility of implementing a group songwriting program with family caregivers of people living with dementia. Fourteen family caregivers consented to participate in either the songwriting group (n=8) or control condition (n=6). Participants completed baseline and 7-week measures of depression (PHQ-9), perceptions of their caregiving experience (PACQ), and perceptions of their relationship with the care recipient (QCPR). A six-session group songwriting program was implemented across two sites, focusing on participants co-creating a song about their caregiving experiences. Participation and retention rates were high suggesting the intervention was acceptable. An observed pre-post effect size for the PHQ-9 in the experimental group (d = .64) and control group (d = -0.33) suggests the measure is sensitive to change over a short period of time in this population and has the potential to detect significant change in a larger controlled trial. Qualitative analysis of focus group interviews suggested the songwriting process allowed participants to share their entire caregiver journey with others, differentiating the intervention from standard carer support groups. Participants described group songwriting as enabling them to find connections with other caregivers, create a group identity, and gain insight into their carer journey, subsequently leading to the development of inner strength and personal growth. Qualitative findings suggest coping may be a more relevant construct to measure than caregiver-patient relationship quality or caregivers’ perception of caregiving.